PERANCANGAN SISTEM INFORMASI HARGA POKOK PRODUKSI DENGAN METODE BIAYA ACTIVITY BASED COST SYSTEM PADA PT. ASELI DAGADU DJOGDJA - Dinik Fitri Rahajeng Pangestuti (Universitas Ahmad Dahlan, 2016)
Rapid development of information technology and business realizes companies to put information as the major need. A good information system will help decision maker to run their duties faster, more quickly and more accurately. A good accounting information system can be used also to arrange the using of economical resaources had by companies to be more efficient and effective. In manufacture industries, have many varieties costing method to apply. ABC System is one of the costing calculation alternative which is relatively proper for manufacture industries having a relatively high diversity of product. Thus, to implement ABC system in manufacture industries will be complicate, in order it needs a tool to support the decision. Designing information system will give solution to the problem. This research use FAST (Framework for the Application of System Thinking) methodology promoted by Bentley and Whitten in their book title is System Analysis and Design for Global Enterprises to design productioninformation system. By designing production information system will give information of cost of goods manufactured with ABC System approach and another important thing to help in the making desicion and give the optimal serving to customer.